"When will They Ever Learn"? Selective Discrimination in Provision of Schooling Facilities in Muslim Majority Areas: A Case Study of Murshidabad District of West Bengal, India. Issue 1 (2nd January 2016) - Das, Arijit
Abstract: Inequality in educational attainment among various religious communities in India has come to light in the public domain only after the publication of Sachar Committee Report. The committee opined that selective discrimination of schooling facilities in Muslim concentrated areas is one of the major reasons behind the low educational attainment of that community. The present study aims at understanding the disparities in the provision of schooling facilities in Muslim-dominated and non-Muslim-dominated regions of West Bengal considering Murshidabad district as the study area. The present study constructed an Educational Development Index by considering 11 socioeconomic indicators and using the principal component analysis method, applied it to the study population. It has been found that the blocks having a higher share of Muslim population registered lower levels of educational development. It has also been found that most of the deprived schools located in the Muslim-dominated areas and within the non-Muslim-dominated areas the schools having higher share of Muslim pupil are mostly deprived.